Art paintings accessible to the blind - Kermauner, Aksinja (Array, 2021)
The purpose of the article is to explore in what ways visual arts can be brought closer to blind persons in the postmodern society, in which sight is perceived to be the highest of the senses and in which most information is based on images. The basic methods of presenting a work of art involve the remaining senses, mostly those of hearing and of touch. It is of course not enough just to deliver a factual description of a painting or to transform it into tactile graphics – more complex techniques such as audio-description, method of associations, participating in role-playing, all with the aim of a holistic experience of the work of art, must be sought instead.